Management Control Systems and Partnerships in Driving Innovation and Business Performance: A Systematic Literature Review - Ingrid Panjaitan; Ika Rosenta Purba (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The increasing complexity of business environments driven by digital transformation and sustainability challenges has heightened the importance of understanding how management control systems and alliance strategies jointly influence innovation capacity and business performance. Therefore, this study aims to conduct a systematic literature review and synthesize recent research on the interrelationship between management control systems, alliance strategies, innovation, and firm performance to identify emerging themes, research gaps, and theoretical contributions. Using the PRISMA approach, 22 peer-reviewed articles published between 2020 and 2025 were selected from the Scopus, Web of Science, and DOAJ databases and analyzed for conceptual and methodological insights. The findings reveal that management control systems and alliance strategies play a significant role in enhancing innovation capability and improving business performance, while digitalization and sustainability emerge as crucial contextual determinants. However, existing studies have yet to fully explain how these constructs dynamically interact within technology-driven and uncertain environments to support sustainable innovation. Based on this synthesis, the study proposes a conceptual model integrating management control systems and alliance strategies to achieve superior innovation and performance outcomes and suggests that future research employ longitudinal and cross-industry designs to validate and extend the proposed framework.